Feasibility of on-board hydrogen production from hydrolysis of Al-Fe alloy for PEMFCs - Eom, KwangSup; Cho, EunAe; Kwon, HyukSang (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The feasibility of using the hydrolysis of Al alloys in an on-board hydrogen generation system for PEMFCs is investigated. Hydrogen produced by the hydrolysis of Al-Fe alloys is supplied directly to a PEMFC. The weight-normalized hydrogen generation rate of sheet Al-1Fe is higher than that of cubic Al-1Fe alloy, and its hydrogen generation rate changes little during hydrolysis in alkali water. Furthermore, during the hydrolysis reaction, the water temperature is stable. Hence, Al-1Fe in sheet form is suitable as a source for on-board hydrogen production from hydrolysis in alkali water. At a current of 10 A, the PEMFC presents a voltage of about 0.71 V, which remains stable for 37 min. However, after 37 min, the cell voltage decreases dramatically to 0 V due to a reduction in hydrogen feeding rate by exhaustion of Al-1Fe. It is particularly notable that on-board hydrogen production using the hydrolysis of Al-Fe alloy exhibits self-humidification, supplying humidity automatically without a humidifier. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: FUEL-CELL; BOROHYDRIDE SOLUTION; SODIUM-BOROHYDRIDE; ALUMINUM-ALLOYS; GENERATION; KINETICS